2021
DOI: 10.1021/acsnano.1c02079
|View full text |Cite
|
Sign up to set email alerts
|

Reversing the Irreversible: Thermodynamic Stabilization of LiAlH4 Nanoconfined Within a Nitrogen-Doped Carbon Host

Abstract: A general problem when designing functional nanomaterials for energy storage is the lack of control over the stability and reactivity of metastable phases. Using the high-capacity hydrogen storage candidate LiAlH4 as an exemplar, we demonstrate an alternative approach to the thermodynamic stabilization of metastable metal hydrides by coordination to nitrogen binding sites within the nanopores of N-doped CMK-3 carbon (NCMK-3). The resulting LiAlH4@NCMK-3 material releases H2 at temperatures as low as 126 °C wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 49 publications
1
34
0
Order By: Relevance
“…A series of notable advances have been observed for complex hydrides as well, although their details are beyond the scope of this review. In short, metal tetrahydridoaluminates/alanates [14,51]: LiAlH 4 [54,81,96,99,101,111,113,135,166,178], NaAlH 4 [33,45,50,69,74,82,[127][128][129]167,214,234,235], tetrahydridoborates/borohydrides [3,12,14,42]: LiBH 4 [42,45,47,54,56,70,78,81,87,89,91,93,99,100,104,106,108,120,123,130,…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A series of notable advances have been observed for complex hydrides as well, although their details are beyond the scope of this review. In short, metal tetrahydridoaluminates/alanates [14,51]: LiAlH 4 [54,81,96,99,101,111,113,135,166,178], NaAlH 4 [33,45,50,69,74,82,[127][128][129]167,214,234,235], tetrahydridoborates/borohydrides [3,12,14,42]: LiBH 4 [42,45,47,54,56,70,78,81,87,89,91,93,99,100,104,106,108,120,123,130,…”
Section: Discussionmentioning
confidence: 99%
“…Improvements on hydrogen release/uptake cycles have often been explored in conjunction with utilization of catalysts used to either dope the host, or the hydride material. This strategy is based on formation of active sites for hydrogenation reaction to occur, or is sometimes ascribed to the formation of a reactive intermediate species [19,68,92,102,[111][112][113]117,125,128,151,160,161,163,[195][196][197]. In addition, cation substitution or anion substitution in complex hydrides has been employed to reduce energy barriers and improve overall recyclability of the hydride materials (Table 8).…”
Section: Mxenementioning
confidence: 99%
“…So far, the methods to improve the properties of light metal hydrides mainly include nanocrystallization, [17,18] doping, [19][20][21][22][23] and compositing. [24][25][26][27][28] Among them, catalyst-doping is considered to be the optimal means which presents plentiful superiorities for decreasing metal-H bond energy. [29] Zhang et al synthesized 3D flowerlike TiO 2 @C, successfully decreasing the onset and the peak temperatures of TiO 2 @C-doped-MgH 2 to 180.3 and 233.0 °C.…”
Section: → +mentioning
confidence: 99%
“…So far, the methods to improve the properties of light metal hydrides mainly include nanocrystallization, [ 17,18 ] doping, [ 19–23 ] and compositing. [ 24–28 ] Among them, catalyst‐doping is considered to be the optimal means which presents plentiful superiorities for decreasing metal–H bond energy. [ 29 ] Zhang et al.…”
Section: Introductionmentioning
confidence: 99%
“…[11] However,s tabilization of an unstable metal hydride was demonstrated only recently by infiltrating nitrogen-doped CMK-3 with LiAlH 4 . [12] Previously,i tw as shown that H 2 release by AlH 3 can be accelerated by confinement in nanoporous carbon, but reversibility remains ap roblem. [13] Covalent organic frameworks (COFs) [14] and metal-organic frameworks (MOFs) [15] are more attractive hosts for nanoconfining metal hydrides than porous carbon due to their highly tailorable pore functionalities.…”
Section: Introductionmentioning
confidence: 99%